The Essays of Contaminated Landscapes - Tomczok, Paweł (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The article presents an analysis of the essayistic knowledge about genocide. For this purpose, the author used works by Martin Pollack. Further, the article indicates the intertwining of two threads in Pollack’s prose. The first one is the history of his family, recollections about Nazi relatives, and the dissonance which formed inside him regarding his family’s past. The other one is the study of space understood as uncovering its “contamination”, the sinister past which has marked the specific portion of the landscape. The aim of the article is to check whether it is possible to decontaminate, i.e. expunge that contamination from these landscapes in order to make them once again locations which foster life rather than are mere empty cemeteries.